Fault Location Algorithm for Three-Terminal Transmission Line with unknown Line Parameters - Nguyen, Xuan Vinh; Nguyen, Xuan Tung; Nguyen, Duc Huy (Old Journal, 2017)
This paper presents an algorithm used to locate fault on three-terminal transmission lines. The algorithm utilizes voltage and current data measured at line terminals and does not require any line parameter for determining fault location. Proposed algorithm consists of two steps: determining the line parameters and locating the fault. The algorithm can apply for homogeneous or non-homogeneous tapped lines. Presented algorithm has a solid mathematical basis, the accuracy and efficiency of the algorithm was well validated through results of simulation in Simulink/Matlab.